2008
DOI: 10.1158/1541-7786.mcr-08-0224
|View full text |Cite
|
Sign up to set email alerts
|

Notch Inhibits Expression of the Krüppel-Like Factor 4 Tumor Suppressor in the Intestinal Epithelium

Abstract: The zinc finger-containing transcription factor, Krü ppel-like factor 4 (KLF4), inhibits cell proliferation. An in vivo tumor-suppressive role for KLF4 is shown by the recent finding that Klf4 haploinsufficiency in Apc Min/+ mice promotes intestinal tumorigenesis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 49 publications
(97 reference statements)
5
94
2
Order By: Relevance
“…Because KLF4 has an important role in many biological processes, its expression may be regulated by many different regulators (21,44). Therefore, miR-10b, as one of its post-transcriptional regulators, could partly influence its protein level but may not have a correlation with its expression level.…”
Section: Discussionmentioning
confidence: 99%
“…Because KLF4 has an important role in many biological processes, its expression may be regulated by many different regulators (21,44). Therefore, miR-10b, as one of its post-transcriptional regulators, could partly influence its protein level but may not have a correlation with its expression level.…”
Section: Discussionmentioning
confidence: 99%
“…The incompetence of DN2 cells leads to a block at the DN2-to-DN3 transition in Klf4Tg mice. In humans, NOTCH signaling downregulates KLF4 expression in the gut [30][31]. Interestingly, Notch signaling is also a positive regulator of T cell lineage and Notch ligands are found on stromal cells throughout the thymus [5,32].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between Notch receptors and their ligands (Jagged 1 and 2 and Delta-like 1, 3 and 4) results in proteolytic cleavage of Notch by a γ-secretase, which releases the Notch intracellular domain (NICD) from the plasma membrane, initiating a subsequent nuclear forms a complex with one of three transcriptional regulators, including CSL [collectively referring to C-promoter binding factor (CBF)-1, Suppressor of Hairless in Drosophila, and Lag-1 in Caenorhabditis elegans also known as recombination signal-binding protein Jκ(RBP-Jκ)], mastermind (MAML)-1 and p300/CBP, followed by transcriptional activation of a set of target genes, including the hairy enhancer-of-split (Hes) gene family (Iso et al, 2003;Katoh and Katoh, 2007). Since Hes-1 is a transcriptional repressor, Notch signaling negatively regulates the Krüppel-like factor 4 (KLF4) through its activation of Hes-1 expression (Ghaleb et al, 2008). KLF4 is highly expressed in terminally differentiated epithelial cells in the colon (Shields et al, 1996) and is also believed to be a tumor suppressor gene (Abbas and Dutta, 2009).…”
Section: Notch Signaling and Colon Cancermentioning
confidence: 99%
“…It was also reported that the activation of Notch signaling is essential for the development of adenomas in APC Min/+ mice (van Es et al, 2005) and self-renewal of tumor-initiating cells (Sikandar et al, 2010). Importantly, Hes1 is known to suppress the expression of Krüppel-like factor 4 (KLF4), a transcriptional repressor (Ghaleb et al, 2008). KLF4 is a zinc finger-containing transcription factor that is highly expressed in terminally differentiated epithelial cells of the intestine (Shields et al, 1996;Dang et al, 2000).…”
Section: Notch Signaling and Colon Cancermentioning
confidence: 99%